Kedudukan Aset Milik Pihak Ketiga Yang Dijadikan Sebagai Boedel Pailit Oleh Kurator Berdasarkan UU Kepailitan Dan UU Hak Tanggungan - Nyulistiowati Suryanti; Pupung Faisal; Salsabila Muharani (Legal Spirit, 2022)
Mortgage is one type of guarantee that lenders are interested in offering loan facilities for because it is seen as a good guarantee and simple to implement. In reality, the guarantee granted by the Debtor to the Creditor bound by this Mortgage does not always belong to the Debtor but rather to a Third Party who has hand over their assets as guarantee for the payment of the Debtor's obligation. Of course, this only becomes a problem if the debtor is unable to repay the creditor; in that case, the creditor may decide to use the bankruptcy process as the last resort to address the debt issue. There are frequently issues with the Curator's power to add all assets connected to the Debtor's assets, including Third Party assets pledged as collateral, to the bankrupt estate. With reference to the Law Number 37 of 2004 on Bankruptcy (K-PKPU Law)  and Law Number 4 of 1996 on Mortgage, this study intends to perform a deeper analysis relating to the authority of the Curator as well as the situation of assets belonging to Third Parties bound by Mortgage in the bankruptcy case. This study was put together using a qualitative method and a normative juridical approach. Data were collected online through a literature review, and they were processed in an analytical descriptive way. The findings of this study show that, first, the new Curator has the ability to enter  Third Party assets if, after two (two) months, Separatist Creditors have not exercised their right to execution as provided for in Article 59, paragraphs (1) and (2) of the K-PKPU Law. Second, under Article 59(1) of the K-PKPU Law, which refers to the principle of lex posteriori derogat legi priori and views the context of the case as bankruptcy, the Curator is actually given the authority to conduct auctions due to the position of assets belonging to Third Parties in the bankruptcy estate, then to resolve this case related to the position of Third Party assets in the bankruptcy estate refers to the K-PKPU Law.